Penerapan Wealth Management: Studi Kasus ppada Keluarga Mr. Ben - , Rizky Yusviento Pelawi; , I Wayan Nuka Lantara, S.E., M.Si., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is a case study with one client. The client in this research is Mr. Ben family (pen name). Mr Ben is a businessman in the sector of cargo service in Jakarta and his wife is a notary public in south Jakarta. Mr. Ben is 53 years old and his wife is 48 years old. The main problem of this research is the growth of assets to prepare the pension of the husband and wife. The evaluation and data analysis is based on the financial data and risk tolerance of the client and his wife. The risk tolerance measuring shows that the client is a conservative while his wife is very conservative. The portfolio rebalancing then is done based on the risk tolerance measuring above. In the process of rebalancing, it is proposed two scenarios based on the risk tolerance of both the client and his wife. From both the scenarios offered, the client and his wife prefer the second scenario with lower risk, but it has better return than the current portfolio.